1970
DOI: 10.1139/v70-073
|View full text |Cite
|
Sign up to set email alerts
|

Studies of specifically fluoridated carbohydrates. Part V. Derivatives of 3,6-anhydro-5-deoxy-5-fluoro-1,2-O-isopropylidene-α-L-idofuraeose

Abstract: The facile synthesis of 3,6-anhydro-5-deoxy-5-fluoro-1,2-O-isoprcpylidene-cc-~-idofuranose (4) from readily available precursors is described. The 'H and 19F nuclear magnetic resonance spectra of this derivative have been analyzed. Interestingly, the fluorine substituent exhibits detectable spin coupling with all ring protons except H-2. Both of the anomeric 1,2-di-0-acetyl derivatives of (4) IntroductionWe have previously described (2, 3) studies of pyranosyl fluoride derivatives which illustrate the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The general methods used, followed those of earlier studies (1). Most of the furanosyl fluoride derivatives were available from other studies (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general methods used, followed those of earlier studies (1). Most of the furanosyl fluoride derivatives were available from other studies (6).…”
Section: Methodsmentioning
confidence: 99%
“…Although these com- 'For Part V see ref. 1. 'Recipient of a n NRCC Scholarship, 1968Scholarship, -1969 ments apply regardless of the absolute accuracy of the method being used, we shall center our discussioil on the n.m.r.…”
Section: Introductionmentioning
confidence: 99%
“…Vicinal Coupling Constants 3J(H,F) in the System F-C-C-H. Vicinal ,9F-1H coupling constants parallel the general stereospecificity of vicinal 1H-1H couplings and are positive in sign. 207 Hall and associates (ref 25, 44, 83, [204][205][206][208][209][210][211][212][213][214][215][216] later examined this relationship in a large variety of fluorinated sugar derivatives and indeed found that the vicinal coupling, 3J(19F,H), is stronger for the atoms in antiparallel orientations, J(180°) = 24 Hz, than when the atoms are in gauche relationship. A very high dependence of coupling on torsion angle in the range about 50-70°seems evident from the observation that the vicinal coupling in structures of type 56 (axial fluorine, equatorial hydrogen) is in the range 1-1.5 Hz but in the range 7.5-12.6 Hz for compounds of type 57 (equatorial fluorine, axial hydrogen).…”
Section: 'C1'mentioning
confidence: 98%
“…Hydrogenolysis of the benzyl group of 14 in the usual manner yielded methyl 2-benzamido-2,6-dideoxy-6-fluoro-a-D-galactopyranoside (IS), which was isolated as its crystalline diacetate (16). Acetolysis of the N-benzoyl group in 16 with a boiling mixture of acetic anhydride and acetic acid afforded methyl 2-acetamido-3,4-di-0-acetyl-2,6-dideoxy-6-fluoro-a -D-galactopyranoside (17) in 74% yield, de-0-acetylation of The 4,6-di-0-mesylglucopyranoside (4) was a suitable precursor of 2-amino-4,6-difluoro-2,4,6-trideoxy-a-D-galactopyranoside derivatives by prolonged treatment with tetrabutylammonium fluoride in acetonitrile for several days. The 19F nrnr spectrum of the crude concentrated reaction mixture showed the expected triplet of doublets due to F-6 at 73.3 ppm and a doublet of triplets due to F-4 at 61.7 ppm above external C6F6.…”
mentioning
confidence: 99%